Gerakan Darul Islam: Catatan Kecil dari Pengalaman Sejarah - Ghofar Asnanto (SIASAT, 2019)
On 7 August 1949 NII was officially proclaimed in the village of Cisampang. As a state based on Islam, Kartoswirjo and his friends formed a constitution which he called Kanun Azazy. His government is called a republic. Its leader is called the Imam (Imamate Council). And form an advisory board or fatwa council whose job is to advise the government. The NII continued to survive, and even expanded its strength in the years after its formation in the late 1950s, even reaching its peak in the late 1957s. When his troops reached 13,129 with firearms around 3000. At that time there was no soldier of the Republic of Indonesia who dared to go into the Darul Islam region which was declared de facto. In Tasikmalaya they control almost 1/5 of the population.